2004
DOI: 10.1126/science.1096268
|View full text |Cite|
|
Sign up to set email alerts
|

Antigen Bias in T Cell Cross-Priming

Abstract: Activated CD8+ T cells detect virally infected cells and tumor cells by recognition of major histocompatibility complex class I-bound peptides derived from degraded, endogenously produced proteins. In contrast, CD8+ T cell activation often occurs through interaction with specialized antigen-presenting cells displaying peptides acquired from an exogenous cellular source, a process termed cross-priming. Here, we observed a marked inefficiency in exogenous presentation of epitopes derived from signal sequences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(121 citation statements)
references
References 25 publications
7
111
3
Order By: Relevance
“…We used LyUV treatment of the ADC because it fully inactivated the virus and allowed for efficient NP396 crosspresentation similar to HEK-NP cells [7,8]. We initially expected that GP33 would fail to cross-present because it is located in the signal peptide of LCMV-GP [12], but it was cross-presented with low efficiency, probably due to its exceptional long half-life of 6 h [15]. Although NP396, located in the long-lived nucleoprotein [21], was efficient at cross-presentation, NP205 was poor, possibly due to inefficient processing by the phagosomal/proteasomal machineries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used LyUV treatment of the ADC because it fully inactivated the virus and allowed for efficient NP396 crosspresentation similar to HEK-NP cells [7,8]. We initially expected that GP33 would fail to cross-present because it is located in the signal peptide of LCMV-GP [12], but it was cross-presented with low efficiency, probably due to its exceptional long half-life of 6 h [15]. Although NP396, located in the long-lived nucleoprotein [21], was efficient at cross-presentation, NP205 was poor, possibly due to inefficient processing by the phagosomal/proteasomal machineries.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, much of what is known about the cross-presentation of virus antigens is derived from studies relying on antigen donor cells (ADC) transfected with a single virus protein [7][8][9][10]. The ability of antigens to escape cytosolic degradation in ADC is important during cross-presentation [7,[11][12][13]. Interestingly, it appears that the capacity of an epitope to access cross-priming may support its immunodominance when considering the overall hierarchy [8,10,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the efficiency and specificity of priming will be increased due to the higher tumor antigen load in situ relative to that collected in the draining lymphoid tissues [16] and second, a broader repertoire of tumor-specific naïve T cells is recruited to the site of tumor antigens, leading to a more comprehensive response [35,41]. It has been shown that some tumor antigens may not be efficiently cross-presented due to the antigen bias in T cell cross-priming [42]. In these instances, we have demonstrated in our experimental system using the tumor cell line Ag104L d -LIGHT that certain antigens are presented to and activate naïve T cells within the tumor via a direct presentation mechanism [40,43].…”
Section: Light Creates Lymphoid-like Tissues Inside the Tumor To Imprmentioning
confidence: 99%
“…59,70 It has been demonstrated that some tumor antigens may not be efficiently crosspresented due to the antigen bias in T-cell cross-priming. 71 Furthermore, no additional migration steps are required for CTLs to reach the site of effector function, which leads to the appearance of activated tumor-reactive T cells in a short period of time. In support of this reasoning, we demonstrated in our experimental system using the tumor cell line Ag104L d -LIGHT that certain antigens are presented to and activate naive T cells within the tumor via a direct presentation mechanism.…”
Section: Targeted Immunotherapy To Primary Tumor Tissues Can Generatementioning
confidence: 99%